Learning Problems Facing Nursing Students During the Covid-19 Pandemic - Iqmah, Muhammad Khabib Burhanudin; PH, Livana; Mulyani, Sri (Indonesian Journal of Global Health Research, 2021)
Currently learning is done online, this is due to the covid-19 pandemic that is happening in the world. Online learning causes stress for students, especially nursing students. The study aimed to identify learning problems faced by nursing students during the covid-19 pandemic. It was conducted on 144 nursing students in the city of Kendal. Qualitative research with phenomenological design and quantitative research with analytical descriptive design was carried out using a questionnaire in the form of questions. The research data were analyzed using the Colaizzi method and then the results of the themes obtained were analysed univariate using a frequency distribution. The results of the study found 8 problems, namely a lot of coursework; difficulty understanding the explanation of the material from the lecturer; no field practice and can only apply online practice with limited tools; creation of video assignments; unstable signal network; internet quota; bored; online learning. The majority of problems that occur during online learning during the Covid-19 pandemic are a lot of college assignments.